2003
DOI: 10.1002/ijc.11215
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of CC531 colon carcinoma cells reveals similar regulation of β‐catenin target genes by both butyrate and aspirin

Abstract: The CC531 cell line has been widely used to study different aspects of tumor growth and metastasis and provides an excellent experimental platform to develop novel antitumor strategies. To characterize the CC531 model at the molecular level, we screened for mutations in genes covering important signal-transduction pathways that are known to play major roles during colon carcinogenesis, the wnt and the ki-ras signaling pathways. We found both a prototypic ␤-catenin (Ctnnb1) mutation (Thr 41 Ile) and a ki-ras (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 56 publications
5
27
0
1
Order By: Relevance
“…Based on the present results together with those of previous studies [5,6,[9][10][11][12][13][14], we suggest that a decrease in cell cycle-related genes in cluster IV (Table S2) may be closely associated with the cell growth arrest induced by SB. Of particular interest is our identification of the cell cycle-associated genetic network whose core contains CCND1, PCNA and BRCA1 (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Based on the present results together with those of previous studies [5,6,[9][10][11][12][13][14], we suggest that a decrease in cell cycle-related genes in cluster IV (Table S2) may be closely associated with the cell growth arrest induced by SB. Of particular interest is our identification of the cell cycle-associated genetic network whose core contains CCND1, PCNA and BRCA1 (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…We have also shown that low levels of aspirin are more toxic to colorectal cancer cells than other cancer types such as glioma (U373MG) and breast cancer (MCF-7, MDA-231-MB) cells (data not shown). We were particularly interested in the effect of aspirin at relatively low levels (~1 mM) in comparison to other studies where microarray analysis has been utilised [see for example (30,31)], because we wished to ensure that the results obtained were as physiologically ----------------------------------------------- Table I. Continued.…”
Section: Resultsmentioning
confidence: 99%
“…Microarray analysis has been extensively utilised to examine alterations in gene transcription in response to NSAID exposure in a number of colon cancer cell lines with a subsequent large list of alterations in gene expression reported (24,(28)(29)(30)(31). This study aimed to investigate the relationship between aspirin and DNA repair genes, utilising a commercially available PCR array to analyse the expression of 84 different genes involved in DNA damage signalling pathways in the colorectal cancer cell line SW480 upon aspirin treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Germann et al observed that 4·5 mM butyrate treatment of CC531 rat colon carcinoma cells resulted in positive modulation of expression of four WNT pathway target genes (CCND1, c-MYC, FOSL1 and FST), which have been reported to be up-regulated in CRC (40)(41)(42) . However, the effects of butyrate on c-MYC expression are complex.…”
Section: The Effects Of Resistant Starch and Butyrate On The Expressimentioning
confidence: 99%